Percepção da amamentação em mães pediatras Brenda Miranda Aidar - Brenda Miranda Aidar; Isabela Louise Caldeira Silva; Mariana Bratz da Silva (UniEVANGÉLICA, 2018)
Objective: The objective of this study was to estimate the prevalence of the Hepatitis B and C in drug users who were being treated in rehabilitation centers in the city of Anapolis, Goias. Methods: A quantitative cross-sectional study was performed, with the administration of a questionnaire and short tests. Results: Altogether, 144 patients were studied, all male and with average age of 37.4 years old. The study found four cases of seropositivity for Hepatitis C (2,8%) and none of Hepatitis B. It was noticed significant relation (p<0.05) between Hepatitis C and the variable "used pipe, can or cup to smoke crack and/or similar substances"; the same did not happen with the variables "to use injectable drugs", "to be arrested", "to have sexual relations with the same or with eventual partners", "to receive money or drug as payment for sex" and "to have sexual relations with same sex partner". Conlusions: The study concluded that it is relevant to estimate the prevalence of Hepatitis B and C in a population of drug users, in order to establish public policies for prevention, control and treatment of this risk population.